1994
DOI: 10.1159/000462531
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Lea and Le^b Antigens in Human Saliva

Abstract: We have measured the H type 1, Le^a and Le^b antigens in the saliva from 129 Japanese individuals by a time-resolved europium ion fluorometric immunoassay using artificial antigen-albumin complexes as the reference substances. We confirmed that the amount of Le^b was larger than that of Le^a in the saliva from secretors (Le^a-b+) and vice versa in the saliva from nonsecretors (Le^a+b-). Unexpectedly, we discovered appreciable amounts of Le^b with small amounts of H type 1 in the saliva from the nonsecretors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The Lewis antigens are not intrinsic to red blood cells but are absorbed onto red blood cell membranes from the plasma. Accordingly, typing of Lewis phenotypes is difficult and is sometimes misjudged because of weak hemagglutination as a result of the small numbers of the antigens on red cells, and low titers and low specificities of anti-Le a and anti-Le b antibodies (Good et al 1992;Wang et al 1994). Therefore, it is important and useful to determine the genotypes of the Lewis system.…”
Section: Hao Pang · Yuhua Liu · Yoshiro Koda · Mikiko Soejima Jingtaomentioning
confidence: 99%
“…The Lewis antigens are not intrinsic to red blood cells but are absorbed onto red blood cell membranes from the plasma. Accordingly, typing of Lewis phenotypes is difficult and is sometimes misjudged because of weak hemagglutination as a result of the small numbers of the antigens on red cells, and low titers and low specificities of anti-Le a and anti-Le b antibodies (Good et al 1992;Wang et al 1994). Therefore, it is important and useful to determine the genotypes of the Lewis system.…”
Section: Hao Pang · Yuhua Liu · Yoshiro Koda · Mikiko Soejima Jingtaomentioning
confidence: 99%
“…The blood group and saliva secretion tests of a para-Bombay individual were performed as described previously [11]. A further 136 randomly selected blood samples were provided by the Japan Red Cross Blood Center in Fukuoka City, and genomic DNA was isolated from peripheral leukocytes by the standard method [12].…”
Section: Blood Typingmentioning
confidence: 99%
“…The a(l,2)fucosyltransferase that forms the H antigen, an essential precursor of the A and B antigens, plays a regulatory role in the tissue expression of the ABO antigens. Several lines of evidence have indicated that at least two a( 1,2)fucosyltransferases are present in human tissues [6, 71. One is the H-type FUTl-encoded a(l,2)fucosyltransferase, which regulates the expression of the H antigen mainly on erythrocyte membranes and the other is the secretortype FUT2-encoded a( 1,2)fucosyltransferase, which regulates the expression of the H antigen mainly in epithelial cells and body fluids such as saliva [4,5,[8][9][10]. FUTI, FUT2, and a FUT2 pseudogene (Secl) have been isolated [ll-131.…”
mentioning
confidence: 99%